Cognitive mechanisms, neural circuitry, and individual differences in human foraging under threat - Trier, H (2023)
In nature, survival often requires foraging while staying vigilant for potential predators. The ability to flexibly switch between foraging and vigilance is ubiquitous across species and thought to have shaped the evolution of neural circuitry in animals. Balancing attention between rewards and threats is also relevant to contemporary human life, and changes in responding to rewarding versus threatening stimuli have been linked with symptoms of psychiatric disorders such as apathy and anxiety. However, it is not fully understood how people make these behavioural transitions. Characterising the cognitive mechanisms, neural substrate, and role of individual differences in this process would improve our knowledge of ecological decision-making and could provide insights of clinical relevance. This thesis aims to address these knowledge gaps by presenting three experiments. First, Chapter 1 introduces relevant background information including theories, methods, frameworks, and questions that inspired the design and interpretation of the following experiments. Next, Chapter 2 presents a unique ecological task for studying natural foraging and vigilance behaviours. I use a computational model to show how people solve this task by tracking information about reward and threat levels, demonstrate model validity with simulation, and show potential clinical relevance. Third, Chapter 3 describes a large online study inspired by computational psychiatry and transdiagnostic approaches. Results show that dimensions of psychiatric symptoms are characterised by distinct patterns in switching between foraging and vigilance, and suggest that emotion plays an adaptive, homeostatic role in decision-making. Chapter 4 presents a study that uses ultra-high field fMRI to map brain areas involved in behavioural transition. It shows that two distinct networks are involved in tracking reward and threat and initiating behavioural change. Finally, a general discussion considers how this work contributes to our knowledge of fundamental cognitive and neural processes and supports emerging methodologies for studying mental health and disease.